Pronominal Variation in Spoken Portuguese in “Rurban” Communities: Reflections on Evaluation, Prestige, and Stigma - Pinto, Letícia Gaspar [UNESP]; Berlinck, Rosane Andrade [UNESP] (Springer Nature, 2023)
Social evaluation of linguistic forms is determinant of the fate of these forms in the linguistic scenario of a community. In this chapter we aim to build reflections on the concept of social evaluation, prestige, and stigma related to linguistic uses from the perspective of a less explored context in variation studies – that of communities with rural characteristics. We focus on the pronominal expression of the first-person plural in the variety of Brazilian Portuguese (BP) spoken in two rural communities in the south of Minas Gerais, Brazil. The study shows that, in addition to the variation between “nós” and “a gente,” general in BP, there is a phonological variation, as the inhabitants of this region also use “nóis” and “nói.” It also reveals that the variants are associated with local values that do not correspond necessarily to those of urban communities.
Keywords: Brazilian Portuguese; Evaluation; First-person plural pronouns; Linguistic variation and change; Rurban communities; Social meanings